2015
DOI: 10.1371/journal.pone.0119338
|View full text |Cite
|
Sign up to set email alerts
|

UNC50 Prompts G1/S Transition and Proliferation in HCC by Regulation of Epidermal Growth Factor Receptor Trafficking

Abstract: BackgroundUNC50 has long been recognized as a Golgi apparatus protein in yeast, and is involved in nicotinic receptor trafficking in Caenorhabditis elegans, but little is known about UNC50 gene function in human biology despite it being conserved from yeast to high eukaryotes.ObjectivesWe investigated the relation between UNC50 and human hepatocellular carcinoma (HCC) and the potential mechanisms underlying HCC development.Methods UNC50 mRNA expression patterns in 12 HCC and adjacent non-cancerous tissues dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…28 BBC3 is a proapoptotic BH3-only protein that can sensitize HCC cells to sorafenib-induced apoptosis. 29 Some tumor-promoting genes such as MYC, 30 EGFR, 31 VEGFA, 32 and NOTCH1 33 are downregulated by PP2Ac silencing. These results offer a molecular insight into the regulation of the aggressiveness of HCC by PP2Ac.…”
Section: Discussionmentioning
confidence: 99%
“…28 BBC3 is a proapoptotic BH3-only protein that can sensitize HCC cells to sorafenib-induced apoptosis. 29 Some tumor-promoting genes such as MYC, 30 EGFR, 31 VEGFA, 32 and NOTCH1 33 are downregulated by PP2Ac silencing. These results offer a molecular insight into the regulation of the aggressiveness of HCC by PP2Ac.…”
Section: Discussionmentioning
confidence: 99%
“…UNC50 now emerges as another protein that plays an important role in regulating GBF1 localization. The process by which these factors cooperatively mediate membrane recruitment of GBF1 under physiological conditions as well as the consequences of changes in activities or levels of one or more of these factors in disease states (e.g., up-regulation of UNC50 in hepatocellular carcinoma; Fang et al, 2015 ) on GBF1 function is another important area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…UNC50 has long been recognized as a Golgi apparatus protein in yeast, and is involved in nicotinic receptor trafficking in Caenorhabditis elegans. In 2015, Fang et al found that UNC50 was correlated with G1/S transition and proliferation in hepatocellular carcinoma via the influencing epidermal growth factor receptor trafficking (47). Interestingly, our data showed that UNC50 was involved with the nigericin damage, which could be cis-regulated by lnc-SLC25A3-3_1.…”
Section: Discussionmentioning
confidence: 60%